2014
DOI: 10.1155/2014/905747
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Expenditure and GDP in African Countries: Evidence from Semiparametric Estimation with Panel Data

Abstract: A large body of literature studies on the relationship between health care expenditure (HCE) and GDP have been analyzed using data intensively from developed countries, but little is known for other regions. This paper considers a semiparametric panel data analysis for the study of the relationship between per capita HCE and per capita GDP for 42 African countries over the period 1995–2009. We found that infant mortality rate per 1,000 live births has a negative effect on per capita HCE, while the proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
(36 reference statements)
3
16
0
Order By: Relevance
“…( Fuchs, 2013 ) concluded that the rate of growth in health care expenditures appears to have been substantially related to the growth of the GDP. ( Lorenzoni, Belloni, & Sassi, 2014 ), ( Rtveladze et al, 2014) , ( Ozturk & Topcu, 2014 ), ( Lv & Zhu, 2014 ), and ( Pascual & Gonzaacute, 2014 ) demonstrated the relationship between health expenditures and economic growth in OECD countries and other regions in the world. The findings of these articles indicate that GDP is the most important factor determining health care expenditures of countries.…”
Section: Introductionmentioning
confidence: 97%
“…( Fuchs, 2013 ) concluded that the rate of growth in health care expenditures appears to have been substantially related to the growth of the GDP. ( Lorenzoni, Belloni, & Sassi, 2014 ), ( Rtveladze et al, 2014) , ( Ozturk & Topcu, 2014 ), ( Lv & Zhu, 2014 ), and ( Pascual & Gonzaacute, 2014 ) demonstrated the relationship between health expenditures and economic growth in OECD countries and other regions in the world. The findings of these articles indicate that GDP is the most important factor determining health care expenditures of countries.…”
Section: Introductionmentioning
confidence: 97%
“…Most of the studies on determinants of healthcare expenditure have used demand function approaches to analyse the factors explaining healthcare expenditures, where healthcare expenditures are hypothesized to be a function of income (Newhouse, 1977) and a selection of non‐income variables such as population density (Crivelli et al, 2006; Hosoya, 2014), population's age structure (Barkat, Mrabet, & Alsamara, 2016; Okunade, Karakus, & Okeke, 2004), foreign aid (Barkat et al, 2016; Murthy & Okunade, 2009) and political stability (Biadgilign et al, 2019; Imoughele & Ismaila, 2013). While some models have applied either cross‐section regression (Murthy & Okunade, 2009) or time series regression (Tajudeen, Tajudeen, & Dauda, 2018), most studies have employed panel data models in both developed countries (Baltagi & Moscone, 2010; Murthy & Okunade, 2016) and developing countries (Barkat et al, 2016; Barkat, Sbia, & Maouchi, 2019; Lv & Zhu, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Angola spends 3.4% of their GDP on healthcare expenditure. Republic of Congo spends 2.5%; Eritrea spends 2.6%, and Kuwait spends 2.7% of their GDP on health compared to the Unites States which spends 17.9% of their GDP [ 1 ]. Developing countries struggle under the burden of human immunodeficiency virus (HIV), tuberculosis and malaria [ 2 ].…”
Section: Introductionmentioning
confidence: 99%